Implementasi Program Agama Keagamaan dan Pendalaman Kitab-Kitab (AKPK) Siswa di SMPN 1 Darangdan - Hanafi, Nanda; Surana, Dedih; Taja, Nadri (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is motivated by the large number of students who have little or no understanding of religious teachings from original sources according to the religion they adhere to. This condition often gives rise to disagreements and is easily provoked by religious issues without clarifying them first, thus causing arguments just to defend their personal opinions. This can be minimized through efforts to increase their religious knowledge and understanding in accordance with the rules of the religion they adhere to. The objectives of this research are: 1. To determine the concept and implementation of the AKPK program at SMPN 1 Darangdan. 2. To find out what are the supporting and inhibiting factors for the AKPK program. 3. To find out students' religious values in the AKPK program book learning. This research uses descriptive qualitative methods. Data collection used is observation, interviews, documentation. The data obtained will be analyzed by reducing the data, explaining the data and drawing conclusions. The research results show that, 1). Implementation of the design of the Implementation of the Religious Program and Deepening of the Books of the Bible (AKPK) Students at SMPN 1 Darangdan, achieving educational goals through four basic POAC functions including; planning, organizing, actuating, and controlling. 2). supporting factors are the existence of AKPK pdf files, AKPK guidebooks and literature books, AKPK managerial aspect teams, and teacher participation in the implementation of AKPK. Among the inhibiting factors is the number of students who are illiterate in Arabic. The solution taken from the obstacles to the implementation of this activity is the addition of AKPK hours. 3). The religious value obtained by students from the AKPK program is to improve relationships in insaniyyah and illahiyyah, students also know the position of worship in life. Abstrak. Penelitian ini dilatarbelakangi banyaknya pelajar yang kurang atau bahkan tidak memahami ajaran agama dari sumber asli sesuai dengan agama yang dianutnya. Kondisi ini sering menimbulkan silang pendapat dan mudah terprovokasi dengan isu-isu keagamaan tanpa melakukan klarifikasi terlebih dahulu, sehingga menyebabkan pertengkaran hanya untuk mempertahankan pendapat pribadinya Hal ini bisa diminimalisir melalui upaya peningkatan pengetahuan dan pemahaman keagamaan mereka sesuai dengan kaidah agama yang dianutnya. Tujuan penelitian ini adalah: 1. Untuk mengetahui konsep dan pelaksanaan program AKPK di SMPN 1 Darangdan. 2. Untuk Mengetahui apa saja faktor pendukung dan penghambat program AKPK ini. 3. Untuk mengetahui nilai religius siswa yang ada di dalam pembelajaran kitab program AKPK.. Penelitian ini menggunakan metode kualitatif deskriptif. Pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi. Data yang diperoleh akan dianalisis dengan cara mereduksi data, memaparkan data dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa, 1). Pelaksanaan desain Implementasi Program Agama Keagamaan dan Pendalaman Kitab-Kitab (AKPK) Siswa di SMPN 1 Darangdan, pencapaian tujuan pendidikan melalui empat fungsi dasar POAC diantaranya; planning, organizing, actuating, dan controlling. . 2). faktor pendukung adanya file pdf AKPK, buku panduan dan buku literatur AKPK, tim aspek manajerial AKPK, dan partisipasi guru dalam pelaksanaan AKPK. Diantara faktor penghambatnya adalah banyaknya siswa yang buta huruf Arab. Solusi yang diambil dari penghambat pelaksanaan kegiatan ini yaitu dengan adanya penambahan jam AKPK. 3). Nilai keagamaan yang didapat siswa dari program AKPK yaitu memperbaiki hubungan secara insaniyyah dan illahiyyah, siswa juga mengetahui kedudukan ibadah dalam kehidupan.